Organisational structure process, market capabilities and effectiven ess of privatised enterprises in Uganda - David
Master of Business administration research proposal.
AR/MISR/56/2/1
English
Shelf no. 1.
Keywords: Free enterprise -- Uganda; Privatization -- Uganda